A construção do ethos discursivo Kaingang em narrativas orais: imagens de si fundamentadas no coletivo - Fumagalli, Rita de Cássia Dias Verdi (2019)
The theme of this thesis is construction of Kaingang discursive ethos in oral narratives. The general objective is to analyze the oral narratives of Kaigang people of Guarita Indigenous Land (RS), located in the municipality of Tenente Portela, Rio Grande do Sul (RS), identifying the scenographies and discursive ethes that emerges from these discourses, both as an individual representation, the image of itself, and as a collective construction, based in the lit flame of ancestry. The theoretical framework on which the study is developed is centered on the theoretical-methodological assumptions of Maingueneau (1997, 1984/2008a, 2008b, 2013, 2014, 2015), especially about the scenographies and ethos discursive concepts; of Donisete and Grupioni (2000) and of Veiga (2006), in the studies about Brazilian indigenous populations; of Vergara (2004) and of Ferreira Netto (2008), about the formulation of the orality and oral narratives notion; of Halbwachs (2006) and of Bosi (1987), in relation to the conceptions of collective memory, besides the conceptual perspectives of cultural identity, according to Hall (2013, 2015, 2016), Candau (2012) and Geertz (2015). The formulated thesis is that the indigenous Kaingang subject, by speaking, mobilize in the oral narratives, an arsenal of meanings from a shared collective memory to (re) construct and re-signify the discursive image of themselves (ethos) and the community to which they belong. This is an exploratory-descriptive research, developed through field research, with qualitative approach. The corpus is made up by three oral narratives, announced voluntarily, by indigenous subjects, members of the Kaingang community, and registered with the use of a recorder and a field journal. The analysis indicates that the scenographies constructed in the oral narratives of the Kaingang indigenous people are supported by the traces of collective memory and cultural identity, in a network woven in interdiscursivity, making the ethos of the indigenous enunciator subject emerge as a discursive image of himself, individual or collective, which surpasses the discourses and the knowledges shared by his community. That is, a discursive image that reflects important aspects of the social, moral and behavioral organization of the Kaingang ethnic group.